Extraction, Encapsulation, and Evaluation of Volatile Compounds from Black Périgord Truffle (Tuber melanosporum) for Innovative Value-added Products - Phong, Win Nee (Curtin University, 2022)
Black Périgord truffle is highly appreciated for its unique aroma, however, its seasonal perishability restricts its year-round availability. To extend the availability of the natural truffle aroma throughout the year, this thesis aimed to explore the potential of extraction and encapsulation techniques to process the black truffle into a natural flavouring ingredient for food application.